3x - y = 12 is the same as 3x - 12 = y, or y = 3x - 12.
Chat with our AI personalities
3x + 2y = 8 This is an equation. It could be the equation of a line.
2x+3y=12 ......1st equation 3x+2y=13 .......2nd equation ____________________________________ multiplying 1stt equation by 3 and 2nd equation by 2 3x(2x+3y=12) 2x(3x+2y=13) _______________________________ now the equations become 6x+9y=36 ...3rd 6x+4y=26 ....4th by solving both equation(substractinf 4th from 3rd) we get.. 5y=10 therefore y=2 and x=3
3X + 6 = 12 subtract 6 from each side 3X + 6 - 6 = 12 - 6 3X = 6 divide each sides integer by 3 (3/3)X = 6/3 X = 2 ------------check in original equation 3(2) + 6 = 12 6 + 6 = 12 12 = 12 checks
Not until it equals something. Equations have equals signs.
6x - 12 = 3x + 15 3x = 27 x = 9